PSYCHOSOCIAL PREDICTORS OF PROSOCIAL BEHAVIOUR AMONG A SAMPLE OF NIGERIAN UNDERGRADUATES - Ayooluwa Afolabi, Olukayode (European Scientific Journal, ESJ, 2014)
Only few psychological researches have actually investigated prosocial behavior among Youths in Nigeria. The other ones have been among children and the aged. Thus, this research looked at the roles of psychosocial factors (religiosity, life satisfaction, perceived social exclusion, family type, type of residence, rural/urban and cultural/ethnic differences) on prosocial behavior among undergraduates. The study makes use of crosssectional survey design that employed a well designed questionnaire with 5 sections. Data was gathered from 440 students from 2 Nigerian Universities. Of the sample, 230 (52.3%) are males and 210 (47.7%) are females with their ages ranging from 19-27years. Results of the 4 hypotheses tested revealed that there were significant relationships among the variables of study. Besides their significant individual contributions to prosocial behavior, religiosity also mediated the relationships between life satisfaction, perceived social exclusion and prosocial behavior. It was also found that respondents residing in a village are more prosocial than those in a city. Lastly, cultural/ethnic differences significantly influence prosocial behavior. The findings were discussed and recommendations made.